2016
DOI: 10.1007/s13205-016-0469-8
|View full text |Cite
|
Sign up to set email alerts
|

Development of novel SSR markers for evaluation of genetic diversity and population structure in Tribulus terrestris L. (Zygophyllaceae)

Abstract: Tribulus terrestris L., commonly called puncture vine and gokhru, is an important member of Zygophyllaceae. The species is highly important in context to therapeutic uses and provides important active principles responsible for treatment of various diseases and also used as tonic. It is widely distributed in tropical regions of India and the world. However, status of its genetic diversity remained concealed due to lack of research work in this species. In present study, genetic diversity and structure of diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 39 publications
2
4
0
Order By: Relevance
“…The mean PIC which represent allele diversity was moderate (0.35) and similar to the report of Kaur et al [35] for Tribulus terrestris but lower to the values reported by Popoola et al [36]. Similarly, the mean percent polymorphism (74.16%) was high and comparable to previous reports on forest trees including P. Biglobosa [35][36][37]. The SSR markers amplified at least two or more than three fragments and recorded a PIC value of 0.35 which is an indicator of high polymorphism.…”
Section: Ssr Markers and Genetic Diversity Of P Biglobosasupporting
confidence: 89%
See 1 more Smart Citation
“…The mean PIC which represent allele diversity was moderate (0.35) and similar to the report of Kaur et al [35] for Tribulus terrestris but lower to the values reported by Popoola et al [36]. Similarly, the mean percent polymorphism (74.16%) was high and comparable to previous reports on forest trees including P. Biglobosa [35][36][37]. The SSR markers amplified at least two or more than three fragments and recorded a PIC value of 0.35 which is an indicator of high polymorphism.…”
Section: Ssr Markers and Genetic Diversity Of P Biglobosasupporting
confidence: 89%
“…The range of alleles (9 -14 alleles) among the markers are comparable to the reports of Lassen et al [26] and higher than previous values on some tree species [33,34]. The mean PIC which represent allele diversity was moderate (0.35) and similar to the report of Kaur et al [35] for Tribulus terrestris but lower to the values reported by Popoola et al [36]. Similarly, the mean percent polymorphism (74.16%) was high and comparable to previous reports on forest trees including P. Biglobosa [35][36][37].…”
Section: Ssr Markers and Genetic Diversity Of P Biglobosasupporting
confidence: 88%
“…The final population structure was calculated with ΔK, based on the second-order rate of change of likelihood distribution mean L″(K) and with respect to K estimated using STRU CTU RE Harvester, it showed a clear peak at optimal K value (Evanno et al 2005;Earl and von-Holdt 2012). Analysis of molecular variance (AMOVA) was conducted to detect the genetic variance within and among subpopulation using GenAlEx Ver 6.5 (Peakall and Smouse 2012;Kaur et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic diversity contributes to a species' ability to cope with environmental change and is often assessed by molecular markers. A variety of molecular markers are used to detect population genetic diversity and differentiation, including restriction fragment length polymorphism (RFLP), amplified fragment length polymorphism (AFLP), and simple sequence repetition (SSR) [39][40][41]. Microsatellites are widely distributed in the genome and have high levels of polymorphism, codominance and repeatability.…”
Section: Discussionmentioning
confidence: 99%